Capillary electrophoresis in a fused‐silica capillary with surface roughness gradient. Issue 19 (7th September 2016) - Horká, Marie; Šlais, Karel; Karásek, Pavel; Růžička, Filip; Šalplachta, Jiří; Šesták, Jozef; Kahle, Vladislav; Roth, Michal
Abstract : The electro‐osmotic flow, a significant factor in capillary electrophoretic separations, is very sensitive to small changes in structure and surface roughness of the inner surface of fused silica capillary. Besides a number of negative effects, the electro‐osmotic flow can also have a positive effect on the separation. An example could be fused silica capillaries with homogenous surface roughness along their entire separation length as produced by etching with supercritical water. Different strains of methicillin‐resistant and methicillin‐susceptible Staphylococcus aureus were separated on that type of capillaries. In the present study, fused‐silica capillaries with a gradient of surface roughness were prepared and their basic behavior was studied in capillary zone electrophoresis with UV‐visible detection. First the influence of the electro‐osmotic flow on the peak shape of a marker of electro‐osmotic flow, thiourea, has been discussed. An antifungal agent, hydrophobic amphotericin B, and a protein marker, albumin, have been used as model analytes. A significant narrowing of the detected zones of the examined analytes was achieved in supercritical‐water‐treated capillaries as compared to the electrophoretic separation in smooth capillaries. Minimum detectable amounts of 5 ng/mL amphotericin B and 5 μg/mL albumin were reached with this method.